2017
DOI: 10.1007/s11274-017-2353-z
|View full text |Cite
|
Sign up to set email alerts
|

Nisin Z produced by Lactococcus lactis from bullfrog hatchery is active against Citrobacter freundii, a red-leg syndrome related pathogen

Abstract: Lactococcus lactis subsp. lactis CRL 1584 isolated from a bullfrog hatchery produces a bacteriocin that inhibits both indigenous Citrobacter freundii (a Red-Leg Syndrome related pathogen) and Lactobacillus plantarum, and Listeria monocytogenes as well. Considering that probiotics requires high cell densities and/or bacteriocin concentrations, the effect of the temperature on L. lactis growth and bacteriocin production was evaluated to find the optimal conditions. Thus, the growth rate was maximal at 36 °C, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Bacteriocins were frequently identified in the microbiomes of amphibians and reptiles, including nisin Z produced by Lactococcus lactis [ 82 , 83 ]. Nisin Z inhibits the growth of the amphibian pathogens Citrobacter freundii and Listeria monocytogenes .…”
Section: Amphibians and Reptilesmentioning
confidence: 99%
“…Bacteriocins were frequently identified in the microbiomes of amphibians and reptiles, including nisin Z produced by Lactococcus lactis [ 82 , 83 ]. Nisin Z inhibits the growth of the amphibian pathogens Citrobacter freundii and Listeria monocytogenes .…”
Section: Amphibians and Reptilesmentioning
confidence: 99%
“…Although studies have shown that amphibian skin secretions contain properties as defense mechanism against chytrid fungus (Niederle et al, 2019; Rollins‐Smith, 2009) and bacteria (Quintana et al, 2017), little is known about the role of secretions as parasite defense mechanisms more generally. Similarly, we know little about how parasitic nematodes find their hosts.…”
Section: Introductionmentioning
confidence: 99%
“…These microorganisms produce a range of antimicrobial metabolites such as organic acids, bacteriocins, diacetyl, and hydrogen peroxide. Bacteriocins are known to inhibit other LAB strains, some Gram-negative pathogens and Gram-positive spoilage bacteria [53,54], as well as moulds and yeasts [55,56].…”
Section: Introductionmentioning
confidence: 99%